Răspuns :
Răspuns:
[tex]\boldsymbol{a) \ \red{f(-3) - f(2) = 5 }}[/tex]
[tex]\boldsymbol{b) \ \red{d(M; G_f) = 2\sqrt{2} }}[/tex]
Explicație pas cu pas:
a) Înlocuim x cu valorile date
f(-3) = -(-3) + 3] = 3 + 3 = 6
f(2) = -2 + 3 = 1
f(-3) - f(2) = 6 - 1 = 5
b) Distanța de la punctul M(-1; 0) la dreapta de ecuație y = -x + 3
⇔ x + y - 3 = 0
[tex]a = 1, b = 1, c = -3, x_{M} = -1 , y_{M} = 0\\[/tex]
[tex]\boxed{\boldsymbol{d(M;d) = \dfrac{\big|a \cdot x_{M} + b \cdot y_{M} + c\big|}{\sqrt{a^{2} + b^{2} }} }}[/tex]
[tex]d(M; G_f) = \dfrac{\big|1 \cdot (-1) + 1 \cdot 0 + (-3)\big|}{\sqrt{1^{2} + 1^{2} } } = \dfrac{\big|-1 + 0 - 3\big|}{\sqrt{1+1} } = \dfrac{\big|-4\big|}{\sqrt{2} } = \\[/tex]
[tex]= \dfrac{4}{\sqrt{2} } = \dfrac{4\sqrt{2}}{2} = \bf 2\sqrt{2}[/tex]